Meadowlark : a coming-of-age crime story - Ruth, Greg; Hawke, Ethan, 1970- (Grand Central Publishing, 2021)
"Set against the quiet and unassuming city of Huntsville, Texas, Jack "Meadowlark" Johnson, and his teenage son, Cooper, embark on a journey of epic proportions. Told over the course a single day, this electrifying graphic novel recounts Cooper's struggle to survive the consequences of his father's mistakes and the dangers they have brought home to his estranged family. As Cooper and his father desperately navigate cascading threats of violence, they must also grapple with their own combative, dysfunctional, but loving relationship"--Provided by publisher.